2020
DOI: 10.1016/j.heliyon.2020.e05807
|View full text |Cite
|
Sign up to set email alerts
|

The role of social media in spreading panic among primary and secondary school students during the COVID-19 pandemic: An online questionnaire study from the Gaza Strip, Palestine

Abstract: Background The rapid outbreak of the COVID-19 pandemic has opened up various issues on social media platforms among school students. The dangerous issue is that misinformation, fake news, and rumours spread on social media faster than reliable information, and also faster than the virus itself, damaging the health systems and affecting the mental health of social media users. Objective The current study aims at determining how social media affects the spread of panic ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
106
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(128 citation statements)
references
References 68 publications
10
106
2
1
Order By: Relevance
“…Buran, & Doğan, 2018). In addition, females are also more likely to express negative emotions, such as anxiety, fear, anger, and depression both alone and in the presence of others, than male (Radwan et al, 2020). This research study was similar to the previous study conducted by Booker, Kelly, and Sacker (2018) which concluded that there were correlations between gender and effects from social media.…”
Section: Discussionsupporting
confidence: 86%
“…Buran, & Doğan, 2018). In addition, females are also more likely to express negative emotions, such as anxiety, fear, anger, and depression both alone and in the presence of others, than male (Radwan et al, 2020). This research study was similar to the previous study conducted by Booker, Kelly, and Sacker (2018) which concluded that there were correlations between gender and effects from social media.…”
Section: Discussionsupporting
confidence: 86%
“…A proportion of studies ( n = 10, 2,321) utilised interviews, of which some were parent interviews ( n = 2, 535), some were child interviews (n = 5, 2,629), and some interviewed both parents and children ( n = 3, 261). Duration of lockdown was 52.3 ± 21.3 days in the included studies (range 30 [ 1 , 4 , 12 , 17 , 25 , 27 , 34 , 39 , 41 , 57 , 82 ]—100 days [ 80 , 100 ]). The characteristics of the included studies and their findings are summarised in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…30.0% of the participants reported a medium negative impact on life-spheres and moderate mental health issues. 15.3% of the sample showed a high negative impact of the COVID-19 lockdown with high mental health issues Radwan et al 2020 [ 82 ] Palestine Cross-sectional 942 66% 6–18 Y ★★ 78.1% of students were psychologically affected. Female students were more psychologically affected, experiencing significantly greater fear than male students ( p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…This has also been stimulating convulsions, miseries and tremor among the people (Hao and Basu 2020 ). Radwan et al ( 2020a , b ) studied how social media generate fear of Covid-19 among the students of primary and secondary school levels in the Gaza Strip, Palestine. The study findings divulge a significant effect of social media spreading tremor among the students, which have an adverse consequence on the mental health and psychological well-being of these school-going students.…”
Section: Review Of Literaturementioning
confidence: 99%